Expression of cancer stem cells markers in urinary bladder urothelial carcinoma and its precursor lesions - Hacek, Jaromir; Brisuda, Antonin; Babjuk, Marek; Zamecnik, Josef (Biomedical papers, 2021)
Background. Cancer stem cells (CSC) and their role in tumorigenesis of various solid tumors have been studied in past decades. Urothelial CSC were first identified 10 years ago and subsequent studies have been performed with the aim to identify reliable markers of CSC. So far, a few studies have investigated a relationship between CSC markers expression in urothelial carcinoma tissue and histopathological characteristics of the tumor. Methods. In our study, we evaluated an immunoexpression of the CSC markers CD24, CD44, CD66 and CD133 in tissue sections of urothelial carcinoma (all tumor grades and stages were included), urothelial carcinoma in situ and non-neoplastic urothelium, totally 218 specimens were enrolled. Results. All studied molecules were expressed either in tumor tissue and non-neoplastic urothelium. Urothelial carcinomas of higher tumor grade and stage expressed molecules CD24 and CD133 significantly more frequently whereas molecules CD44 and CD66 did not show significant association with tumor histopathological features. Conclusions. Our results showed that studied molecules are not suitable for direct detection of CSC in urothelial carcinoma tissue sections, but an expression of molecules CD24 and CD133 is significantly related to urothelial carcinoma grade and stage, which are both important prognostic indicators and therefore an expression of these markers might have a potential prognostic value.
Keywords: cancer stem cells; immunohistochemistry; markers; urothelial carcinoma